WHO WON WOMEN'S SUFFRAGE? A CASE FOR "MERE MEN". (23rd June 2017) - Neuman, Johanna
Abstract : Scholars of women's suffrage have long debated credit, a meditation on which leaders won the campaign to enfranchise American women. Many argue that victory came because of Alice Paul's militancy in picketing the White House. Others insist it was Carrie Chapman Catt's pragmatism in winning state victories. Still others note that both were needed, a political "one-two punch" of strategic effectiveness. This article suggests that one contingent often excluded from this narrative is men. Male suffragists are often portrayed as driven more by a hunger for quixotic political or sexual adventure, or by a chivalrous posture toward women. Examining the records of the New York Men's League for Woman Suffrage and the archival footprints male suffragists left behind, this article argues that whatever their motives, male suffragists made palatable to other men the once radical notion that women could join the coarse, corrupt, and cigar-filled world of politics without losing their femininity—or robbing men of their virility. By their very activism, they conditioned the public to see women—and men—beyond the gendered construct of the domestic sphere and in the light of the interest politics that dominated the Progressive Era.